Dental Approach to Craniofacial Syndromes: How Can Developmental Fields Show Us a New Way to Understand Pathogenesis? - Inger Kjær (Hindawi Limited, 2012)
The paper consists of three parts. Part 1: Definition of Syndromes. Focus is given to craniofacial syndromes in which abnormal traits in the dentition are associated symptoms. In the last decade, research has concentrated on phenotype, genotype, growth, development, function, and treatment. Part 2: Syndromes before Birth. How can the initial malformation sites in these syndromes be studied and what can we learn from it? In this section, deviations observed in syndromes prenatally will be highlighted and compared to the normal human embryological craniofacial development. Specific focus will be given to developmental fields studied on animal tissue and transferred to human cranial development. Part 3: Developmental Fields Affected in Two Craniofacial Syndromes. Analysis of primary and permanent dentitions can determine whether a syndrome affects a single craniofacial field or several fields. This distinction is essential for insight into craniofacial syndromes. The dentition, thus, becomes central in diagnostics and evaluation of the pathogenesis. Developmental fields can explore and advance the concept of dental approaches to craniofacial syndromes. Discussion. As deviations in teeth persist and do not reorganize during growth and development, the dentition is considered useful for distinguishing between syndrome pathogenesis manifested in a single developmental field and in several fields.